EXPLORING THE INTERSECTION OF HEALTHCARE ROLES AND GEOGRAPHICAL DYNAMICS: A MULTIDISCIPLINARY PERSPECTIVE - Salman Mohammed Abdullah Alawad, Ali Abdulmohsen Bandr Binbosayes, Abdulrahman Mohammed Nasser Alyousef, Faisal Saad Altuais, Khalid Mathkar Rasheed Alosaimi, Mubarak Nasser Mubarak Al Dawsari, Khalid Hussain Ahmed Alyami,; Abdulmajeed Awidah Dofian Almutiri, Nasser Saad Abdulaziz Aldosari, Ibrahim Ahmed Alzubaidi, Abdulaziz Shaya Alotaibi (Chelonian Research Foundation, 2022)
This research paper explores the intersection of healthcare roles and geographical dynamics within the context of mental health services in Riyadh, Saudi Arabia. By examining the diverse expertise and perspectives of mental health professionals working in various healthcare facilities across the city, we aim to gain insights into the collaborative nature of mental health care and the impact of geographical factors on service delivery. Through a qualitative analysis of professional roles, interdisciplinary collaboration, and the influence of location on mental health outcomes, this study contributes to the understanding of effective mental health care provision in urban settings.